Pendampingan Remaja dalam Upaya Pencegahan Ide Bunuh Diri - Rohmi, Faizatur; Agustiningsih, Nia; Setiawan, Arik Agung (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Suicidal ideation is a major predictor of suicide in adolescents. Suicide is the second leading cause of death in adolescents Prevention efforts that integrate peer support and school support are still very limited. Objective: The aim of this community service is to increase the knowledge and skills of adolescents regarding strategies for preventing suicidal ideation based on school. Method: This community service activity was held from September 5th to 26th at MTSN 2 Malang. The program involved 73 students. The program consisted of three sessions, once a week, with each session lasting 90 minutes, conducted face-to-face. Interventions provided in schools consist of education and training on danger signs, how to seek help, and coping skills as well as screening. The instrument used to measure suicidal ideation was the PANSI. Result: After being given assistance, there was a significant difference: before being given assistance, there were 4 (5.5%) teenagers in the fairly vulnerable category, in the domain of protecting suicidal ideation, there were 6 (8.2%) in the less category, after assistance, there was 1 person (1.4%) in the vulnerable suicide category and as many as 62 people (84.9%) were in the good suicide ideation protection category. Conclusion: The study results show that adolescents at MTSN 2 Malang are not vulnerable to suicidal ideation. These results highlight the importance of mentoring activities that combine education and targeted training. Integrating mentoring activities in a hybrid format allows for greater flexibility in monitoring adolescents. Investing in a safe, healthy educational environment that supports optimal adolescent development is crucial.